A bi-functional metal-free catalyst composed of dual-doped graphene and mesoporous carbon for rechargeable lithium–oxygen batteries1. Issue 36 (28th September 2015) - Kim, Jae-Hong; Kannan, Aravindaraj G.; Woo, Hyun-Sik; Jin, Dae-Gun; Kim, Wonkeun; Ryu, Kyounghan; Kim, Dong-Won
<x xml:space="preserve">Abstract</x> Nitrogen and sulfur co-doped graphene/mesoporous carbon exhibited high bi-functional catalytic activity toward oxygen reduction and evolution reactions.